Peluang Karier Mahasiswa Perhotelan di Industri Pariwisata Internasional melalui Penguasaan Bahasa Asing - Kadek Ayu Ekasani; Putu Dian Yuliani Paramita; Ida Ayu Gayatri Kesumayathi (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze students’ perceptions of foreign language learning and its impact on their readiness to enter the international job market. The research employed a descriptive qualitative method, collecting data through questionnaires distributed to 100 students from various study programs across multiple faculties. The study explored students’ experiences in learning foreign languages, including perceived challenges, motivations, and the effectiveness of teaching strategies applied in the classroom. The findings indicate that foreign language proficiency has a positive correlation with students’ confidence levels, especially when facing cross-border professional challenges, international collaboration, and communication with global stakeholders. Students reported that while foreign language learning at the university is generally effective, there are areas for improvement, particularly regarding the integration of real-world contexts, industry-specific vocabulary, and interactive practice opportunities. Furthermore, the study revealed that students value opportunities for cultural exposure, international internships, and collaboration with foreign peers as part of their learning experience. Based on these findings, universities are recommended to adopt strategies such as curriculum integration, practice-based teaching methods, interdisciplinary projects, and strengthening international partnerships to better prepare students for global employment. The study concludes that foreign language mastery is not only a linguistic skill but also an essential social, cultural, and professional capital that enhances graduates’ competitiveness in the global job market. Ultimately, developing comprehensive language skills, combined with intercultural competence, will equip students with the adaptability, confidence, and communication abilities required to thrive in diverse international work environments.